(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is dedicated to studying effective ways to integrate innovative technologies into the educational process. Innovative technologies provide an opportunity to enhance the quality of education in the modern education system, making the learning process more interesting and interactive for students. This process serves to enrich the content of education, improve teaching methods, and develop students’ independent thinking abilities.